Investigation of the role of mobile personalisation at large sports events - Sun, Xu; May, Andrew; Wang, Qingfeng (IGI Global, 2017)
This article describes a field study investigating the impact on user experience of personalisation of content provided on a mobile device. The target population was Chinese spectators and the application was large sports events. A field-based experiment showed that provision of personalised content significantly enhanced the user experience for the spectator. Design implications are discussed, with general support for countermeasures designed to overcome recognised limitations of adaptive systems. The study also highlights the need for culturally sensitive methods for requirements capture, design, and data collection during experimentation.